2020
DOI: 10.1109/access.2020.2977464
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of Virtual War Room and Matrix Sketch-Based Streaming Anomaly Detection for Microservice Systems

Abstract: Recently, microservice has been a popular architecture to construct cloud-native systems. This novel architecture brings agility and accelerates the software development process significantly. However, it is not easy to manage and operate microservice systems due to their scale and complexity. Many approaches are proposed to automatically operate microservice systems such as anomaly detection. Nevertheless, those methods cannot be sufficiently validated and compared due to a lack of real microservice systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Mena et al [8] described the micro-services concept for the application of software architecture on IoT devices to acquire data and to maintain the module confguration. Chen et al [9] developed virtual war room model to handle the behavior of micro-service applications including data tracing, fault analysis. In software industry, Akbulut and Perros [10] executed the performance analysis of hardware behavior, time of query response and rate of packet loss for micro-services sketch patterns to reduce infrastructural-risks.…”
Section: A Microservices In Various Sectors and Cia Security Strategymentioning
confidence: 99%
“…Mena et al [8] described the micro-services concept for the application of software architecture on IoT devices to acquire data and to maintain the module confguration. Chen et al [9] developed virtual war room model to handle the behavior of micro-service applications including data tracing, fault analysis. In software industry, Akbulut and Perros [10] executed the performance analysis of hardware behavior, time of query response and rate of packet loss for micro-services sketch patterns to reduce infrastructural-risks.…”
Section: A Microservices In Various Sectors and Cia Security Strategymentioning
confidence: 99%
“…The authors put the mechanism to the test on the SAVI testbed and observed that it could successfully detect anomalous application behavior [67]. Chen et al [38] leveraged resource metrics to find anomalies in the streaming of microservice systems.…”
Section: Dynamic Analysismentioning
confidence: 99%
“…Trace comparison is another possible technique to enact online anomaly detection on multi-service applications instrumented to feature distributed tracing. This is the technique followed by Meng et al [54], Wang et al [88], and Chen et al [17], which all rely on collecting the traces that can possibly occur in a multi-service application and by then checking whether newly collected traces are similar to the collected ones.…”
Section: Trace Comparisonmentioning
confidence: 99%
“…Chen et al [17] instead uses matrix sketching to compare traces and detect anomalies. More precisely, Chen et al [17] adapt an existing matrix sketching algorithm [29] to detect response time anomalies in services in monitored traces.…”
Section: Trace Comparisonmentioning
confidence: 99%
See 1 more Smart Citation